The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1007/s12034-018-1604-4
|View full text |Cite
|
Sign up to set email alerts
|

Physical, optical and structural studies of copper-doped lead oxychloro borate glasses

Abstract: Bluish coloured glasses are obtained from the composition PbCl 2-PbO-B 2 O 3 doped with Cu 2+ ions. Basic physical properties and spectroscopic studies (optical absorption, electron paramagnetic resonance, Fourier transform infrared and Raman spectroscopies) were carried out on these samples. The increase in PbCl 2 content resulted in the decrease in density and increase in molar volume. At optical frequencies, band gaps and Urbach energies were evaluated and their variation is explained. Spin-Hamiltonian para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(20 citation statements)
references
References 40 publications
1
11
0
Order By: Relevance
“…Density plays an important role in understanding the modification of BO 3 into four fold BO 4 units, and vice versa. [1,[34][35][36] In the present study, it was found that the density decreases from 5.236 gm/cc (CZBBCR1) to 4.819 gm/cc (CZBBCR5) with increasing CaF 2 concentration. The molar volume (V m ) was estimated from density and the molecular weight (M) of the glass sample.…”
Section: Density and Molar Volumesupporting
confidence: 53%
See 3 more Smart Citations
“…Density plays an important role in understanding the modification of BO 3 into four fold BO 4 units, and vice versa. [1,[34][35][36] In the present study, it was found that the density decreases from 5.236 gm/cc (CZBBCR1) to 4.819 gm/cc (CZBBCR5) with increasing CaF 2 concentration. The molar volume (V m ) was estimated from density and the molecular weight (M) of the glass sample.…”
Section: Density and Molar Volumesupporting
confidence: 53%
“…From previous literature, the variation in density is explained using the physical parameters like crystal density, molecular weight and/or ionic radius. [1,34,[37][38][39] The gradual enhancement in the mole percentage of CaF 2 in the CZB-BCR glass system caused a nonlinear decrease in the density, which is suitably explained using the crystal density of calcium fluoride (3.18 gm/cc) which is lesser than zinc fluoride (4.95 gm/cc). It can also be assigned to fractional replacement of low molecular weight CaF 2 (78.07 g/mol) by the high molecular weight ZnF 2 (103.406 g/mol).…”
Section: Density and Molar Volumementioning
confidence: 99%
See 2 more Smart Citations
“…In order to understand the role of TM ions in glasses, a powerful technique that characterizes specific physical natures which are sensitive to the local environments can be realized through electron paramagnetic resonance (EPR) spectra, which reveal the microscopic local environment of TM ions in glasses, including the network, symmetries, and bonding conditions around TM ions. 10,14 It is worth mentioning that EPR has been proved highly sensitive to the paramagnetic signals of these TM impurities, which has been adopted to investigate the PbX 2 -PbO-B 2 O 3 glasses (X = F, Cl, and Br) doped with Cu 2+ (3d 9 ), 7,15 represented by the properties of g factors and hyperfine structure parameters, that is, g // > g ⊥ and A // > A ⊥ for Cu 2+ . Despite the investigation of PbCl 2 -PbO-B 2 O 3 -CuO glasses in the previous article 16 and the rough explanation based on simple g formulae with various adjustable molecular orbital coefficients α 2 , β 2 , and β 1 2 , 12,13 the local structural information of paramagnetic impurities Cu 2+ in PbX 2 -PbO-B 2 O 3 glasses (X = F and Br) need to be further studied, which is helpful to acknowledge the role for different TM dopants (Cu 2+ and V 4+ ) by united and compared study.…”
Section: Decomposition Of Raman Spect On Glass Composition From Td Modelmentioning
confidence: 99%